Effect of Thermal Processing on Simultaneous Formation of Acrylamide and Hydroxymethylfurfural in Plum Purée - Oana Emilia Constantin; Kristina Kukurová; Ľubomír Daško; Nicoleta Stănciuc; Zuzana Ciesarova; Constantin Croitoru; Gabriela Rapeanu (Polish Journal of Food and Nutrition Sciences)
The formation of acrylamide (ACR) and hydroxymethylfurfural (HMF) by varying time and temperature for two plum species was performed using a Central Composite Design model. An optimized method for reducing ACR and HMF formation on plum purée thermally treated was designed. The contaminants precursors and their influence in heating of plum purée were also evaluated. The contaminants content was determined on thirteen running variants in the temperature range of 59.3-200.7 °C, and heating time between 5.9 and 34.1 minutes. The model has established that the lowest ACR content was reached at 5.9-minute exposure time and at 130 °C temperature, for both plum species (3.91 µg/kg and 8.73 µg/kg). The lower quantity of HMF was found at 20-min exposure time and at 59.3 °C temperature for both plum species (0.25 mg/kg and 0.18 mg/kg). The results obtained allowed the prediction of the ACR/HMF levels in plum purée for different heating conditions.